Study of Infectious Diseases in Respect of Drugs Therapy: Exploring the impact of medication dosage on antimicrobial resistance and disease control (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Antimicrobial resistance is one of the greatest risks to public health in the 21st century. There is an urgent need for more effective therapy strategies to prevent resistant strains from emerging and spreading. The popular strategy is to handle high-dose patients both to rapidly clear the infection and to reduce the possibility of tolerance. Recent studies have argued that low-dose treatments, at least in some instances, may be more appropriate for reducing antimicrobial resistance within the host. The option of a medication dosage may therefore have implications at the community level, which has so far received little consideration. The impact of the medication dosage on tolerance and disease control are analyzed here.